Evaluation of the Effectiveness of using the Plowshare (Global Journal of Science Frontier Research, 2023)
The article analyzes the life cycle of the plowshare and shows an effective solution to increase the resource The analysis of complex factors affecting the wear of the ploughshare emphasizes their main ones The working condition of the ploughshare is evaluated and the essence of the influencing forces on its wear is revealed A mathematical model for determining the ploughshare resource is derived Having solved the model using the example of a plowshare for different values of their components it is determined that the resource of the plowshare decreases with increasing width and angle of the occipital chamfer and at the same time with increasing width especially in hard soils the resource decrease is observed at a more intensive rate It is established that an increase in the width of the rear chamfer by 1 mm and the angle by 10 reduces the life of the plowshare by 33 and 12 respectively and an increase in the plowing depth by 1 cm reduces the life of the plowshare by 16 It is proved that the reason for the plow surfacing due to an increase in the soil reaction is an increase in the parameters of the rear chamfer A method of reducing the magnitude of the soil reaction is recommended